2018
DOI: 10.3389/fpls.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco BY-2 Media Component Optimization for a Cost-Efficient Recombinant Protein Production

Abstract: Plant cells constitute an attractive platform for production of recombinant proteins as more and more animal-free products and processes are desired. One of the challenges in using plant cells as production hosts has been the costs deriving from expensive culture medium components. In this work, the aim was to optimize the levels of most expensive components in the nutrient medium without compromising the accumulation of biomass and recombinant protein yields. Wild-type BY-2 culture and transgenic tobacco BY-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Noticeably, massive fluorescent aggregates of irregular shapes measuring 5–15 μm in length occurred in the BFA‐treated root cells (Figure c–f). Some of these aggregates, particularly those around the nuclei, were like the perinuclear pleiomorphic aggregates as described earlier in the BFA‐treated BY‐2 cells (Ritzenthaler et al ., ), whereas the others were likely protein bodies formed due to concentrating of the EGFP products in ER, as reported recently for some GFP‐derived proteins overexpressed in tobacco leaves and BY‐2 cells (Hakkinen et al ., ; Saberianfar et al ., ). These changes indicated that BFA treatment successfully blocked the transport of (SP4) 18 ‐EGFP and (SP) 32 ‐EGFP transgene products from ER to Golgi apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, massive fluorescent aggregates of irregular shapes measuring 5–15 μm in length occurred in the BFA‐treated root cells (Figure c–f). Some of these aggregates, particularly those around the nuclei, were like the perinuclear pleiomorphic aggregates as described earlier in the BFA‐treated BY‐2 cells (Ritzenthaler et al ., ), whereas the others were likely protein bodies formed due to concentrating of the EGFP products in ER, as reported recently for some GFP‐derived proteins overexpressed in tobacco leaves and BY‐2 cells (Hakkinen et al ., ; Saberianfar et al ., ). These changes indicated that BFA treatment successfully blocked the transport of (SP4) 18 ‐EGFP and (SP) 32 ‐EGFP transgene products from ER to Golgi apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…Total soluble protein (TSP) was extracted from 100 to 200 mg fresh mass of the infused PCPs and Agrobacterium cells harbouring the respective expression vectors. The cells were frozen in liquid nitrogen in microfuge tubes, ground by bead beating using FastPrep-24 Instrument (MP Biomedicals), dissolved in a double volume of extraction buffer (1 × phosphate-buffered saline; 137 mM NaCl, 2.7 mM KCl, 10 mM Na 2 HPO 4 , 1.8 mM KH 2 PO 4 , pH 7.4), 1 mM EDTA (Sigma Aldrich, St. Louis, MO, United States), 1 × protease inhibitor cocktail (ThermoFisher Scientific) (Häkkinen et al 2018), and again subjected to homogenization using the FastPrep-24 Instrument. The extracts were centrifuged (10,000g at 4 °C) for 15 min and used for further analyses.…”
Section: Protein Extraction and Quantificationmentioning
confidence: 99%
“…takes place under fully controlled sterile conditions in chemically defined media (Häkkinen et al 2018), which allows the production of recombinant proteins according to the current good manufacturing practice (Fischer et al 2005). The high-value product can also be more easily recovered and purified, especially when the product is secreted into the culture medium (Fischer et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that RLK1ox cells may compete in producing proteins more than wildtype cells based on such characteristics as smaller cell size, fast dividing characteristic, and powerful proliferation because it is well known that BY-2 cells can be used as host cells for the large-scale production of recombinant proteins [45].…”
Section: Discussionmentioning
confidence: 99%